AGRO-INDUSTRIAL SUPPLY CHAIN DEVELOPMENT WITH CLUSTER SYSTEM APPROACH: A SYSTEMATIC LITERATURE REVIEW AND FUTURE RESEARCH - Sofiyessi, Ermia; Marimin, Marimin; Eriyatno, Eriyatno; Sutrisno, Sutrisno (International Journal of Supply Chain Management, 2019)
A supply chain is defined as strategic framework which based on network structure, business process and management components. Information and knowledge sharing along with power are focus of relationship mechanism. The purpose of this literature study was to identify factors which influenced in developing of Agro-industrial supply chain with cluster system approach. All this characteristic and possibilities are main areas of interest in cluster concept. The interaction between actors in the supply chain and with other institutions that are mutually synergistic and competing in the proper flow of information within a region transformed through a cluster system approach. The concepts of cluster system indicated efficient instrument to achieve value chain effectiveness and competitive advantages along the supply chain. Through the supply chain and Agro-industrial cluster, collaboration can be definitely increase the competitive advantages of stakeholder which are the key to survive and development of many economic entities and enterprises. Through the cluster system approach, it can identify institutional policies barriers and economic evaluation determinant of the region in the management of Agro-industrial supply chain. The production of high value added of product in the existence of value chain indicated that supply chain management concepts has successfully been implemented within the cluster management system. Keywords cluster system, Agro-industrial, supply chain management, competitive advantages, institutional barriers